1990
DOI: 10.1093/jac/26.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Activity of sub-minimal inhibitory concentrations of aspoxicillin in prolonging the postantibiotic effect against Staphylococcus aureus

Abstract: Aspoxicillin, a newly developed acylureido-penicillin with a long half-life in mouse serum of 55 min, induced postantibiotic effects (PAEs) against Staphylococcus aureus Smith of 1.7 h in vitro and 5.2 h in vivo in a thigh infection model in neutropenic mice. The long serum half-life meant that in order to evaluate the in-vivo PAE, it was necessary to examine the contribution of the drug at a sub-minimal inhibitory concentration (sub-MIC). Growth suppression by sub-MICs of aspoxicillin was examined in vitro us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…This phe nomenon has already been described in this study and has also been studied in vivo [6,29]. Oshida et al [30] observed a reduction in the PAE of aspoxicillin and piperacillin against S. aureus when they injected (3-lacta mase at the beginning of the PAE phase to remove the sub-MICs.…”
Section: Discussionsupporting
confidence: 64%
“…This phe nomenon has already been described in this study and has also been studied in vivo [6,29]. Oshida et al [30] observed a reduction in the PAE of aspoxicillin and piperacillin against S. aureus when they injected (3-lacta mase at the beginning of the PAE phase to remove the sub-MICs.…”
Section: Discussionsupporting
confidence: 64%
“…In an earlier study (27), we demonstrated that when P-hemolytic streptococci in the PA phase were again exposed to 0.2 and 0.3 x MIC after washing, no regrowth was observed for more than 24 h. In contrast, bacteria which had only been exposed to sub-MICs showed growth curves that were almost identical to those of the controls (27). Later, Oshida et al, using the same experimental design, showed that staphylococci in the PA phase were also more susceptible to sub-MICs of ,-lactam antibiotics compared with the controls (30). In the present study we have extended our earlier findings and could demonstrate that also in other antibiotic-bacterial combinations, the effects of sub-MICs on bacteria in the PA phase (PA SME) are much more pronounced than the direct effect of sub-MICs (SME) and than the PAE (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…PAE refers to the suppression of bacterial growth that persists following limited exposure of bacteria to antimicrobial agents and subsequent removal of the antibiotic either by dilution, drug inactivation or repeated washing (Bundtzen et af, 198 1 ;Gerber and Craig, 198 1 ;Vogelman and Craig, 1985). PAE has been demonstrated with Gram-positive (Gerber and Craig, 1981;Oshida et al, 1990), as well as Gram-negative bacteria (Gerber et al, 1982;Isaksson et al, 1988;Pruul and McDonald, 1990). It has to be emphasized that the PAE is due to prior exposure of the organism to antibiotics for a short duration rather than a continuous exposure for a longer period of time as in the estimates of minimum inhibitory concentrations (McDonald et af, 1977;Vogelman and Craig, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of workers have studied the PAE of antibacterial agents against many bacterial isolates (Gerber and Craig, 1981;Gerber et al, 1982;Vogelman and Craig, 1985;Isaksson et al, 1988;Oshida et al, 1990;Pruul and McDonald, 1990;Craig and Gudmundsson, 1996), there is a sparsity of data on the postantifungal effect (PAFE) of antifungals on Cundida species (Craig and Gudmundsson, 1996). and no such information on oral C. albicans isolates.…”
Section: Introductionmentioning
confidence: 99%